Sterically Tuned P‐Phosphanylamino Phosphaalkenes (Me3Si)2C=PN(R)PPh2 and (iPrMe2Si)2C=PN(R)PPh2. Issue 7 (6th April 2018) - Bîrzoi, Roxana M.; Lungu, Daniela; Jones, Peter G.; Bartsch, Rainer; du Mont, Wolf‐W.
Abstract : Deprotonation of the aminophosphanes Ph2 PN(H) R 1a –1h [ R = t Bu (1a ), 1‐adamantyl (1b ), i Pr (1c ), CPh3 (1d ), Ph (1e ), 2, 4, 6‐Me3 C6 H2 (Mes) (1f ), 2, 4, 6‐ t Bu3 C6 H2 (Mes*) (1g ), 2, 6‐ i Pr2 C6 H3 (DIPP) (1h )], followed by reactions of the phosphanylamide salts Li[Ph2 PN R ]2a, 2b, 2g, and2h with the P ‐chlorophosphaalkene (Me3 Si)2 C=PCl, and of2a –2g with ( i PrMe2 Si)2 C=PCl, gave the isolable P ‐phosphanylamino phosphaalkenes (Me3 Si)2 C=PN( R )PPh2 3a, 3b, 3g, and ( i PrMe2 Si)2 C=PN( R )PPh2 4a –4g . 31 P NMR spectra, supported by X‐ray structure determinations, reveal that in compounds2a, 2b, 3a, and3b, with bulky N‐alkyl groups the Si2 C=P–N–P skeleton is non‐planar (orthogonal conformation), whereas3g, 3h, and4g with bulky N‐aryl groups exhibit planar conformations of the Si2 C=P–N–P skeleton. Solid3g and4g exhibit cisoid orientation of the planar C=P–N–C units (planar I) but in solid3h the transoid rotamer is present (planar II). From3g, 4d, and4g mixtures of rotamers were detected in solution by pairs of 31 P NMR patterns (3h : line broadening). Abstract :